Diseño de los sistemas de abastecimiento de agua potable para los barrios: Anita Lucía y Novilleros de la Parroquia de Aloasí, Cantón Mejía. - Bohórquez Barba, Carlos Alexandro (2013)
When designing drinking water supply systems for neighborhoods:   Anita Lucia and Novilleros of the parish of Aloasí, is intended to improve the quality of life   of the residents of the aforementioned neighborhoods, considering that there is currently no   physical infrastructure that allows to supply them with water of good quality.   The designs have been made based on the Water Systems Design Regulations   Potable of the EMAAP-Q., Which have been complemented by the considerations that   establishes the Ecuadorian Construction Code.